Produksi Biodiesel Dari Minyak Goreng Bekas Menggunakan Katalis Abu Tandan Kosong Sawit - Deli, Nur Asma; Sihotang, Antonius Jumadi; Khairiah, Hanifah (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Biodiesel is an alternative diesel fuel made from renewable materials such as vegetable and animal sources. Used cooking oil is waste cooking oil that is often found in households, very easy to obtain and always available all the time. Used cooking oil can be used as raw material for making biodiesel because it contains triglycerides through a transesterification process with the addition of a base catalyst, one of which is the ash of empty palm fruit bunches. This research aims to determine the effect of adding ash from empty palm fruit bunches on making biodiesel from used cooking oil. The method used in this research is transesterification with the addition of a catalyst of empty palm fruit bunch ash varied at concentrations of 1%, 2%, 3%, 4%, 5% with a mole ratio of 1: 6 (oil: methanol). The tests on the biodiesel produced consist of acid number, viscosity and density.